2019
DOI: 10.1093/ajcn/nqz135
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol intake, specific alcoholic beverages, and risk of hip fractures in postmenopausal women and men age 50 and older

Abstract: Background Although a number of studies have examined the association between alcohol intake and hip fractures, few have considered specific alcoholic beverages separately. Objectives We prospectively assessed total alcohol and specific alcoholic beverage consumption and risk of hip fractures in US men and women. Methods Health, lifestyle information, and hip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Although the early paradigm associated with the Mediterranean diet identified moderate alcohol consumption, with red wine as an alcohol source, a growing body of literature shows that the relationship between alcoholic beverages and mortality is rather consistent for both wine and beer, resulting in reduced risk in moderate consumers compared to abstainers or heavy drinkers [44]. Moreover, the results from prospective cohorts suggest that moderate alcohol consumption is inversely associated with risk of hip fractures in middle-aged and older men and women [45]. It should be noted that, in addition to the alcoholic content, these beverages are characterized by a variety of bioactive compounds-mainly polyphenolswhich may explain, at least in part, the potential benefits for health [46].…”
Section: Discussionmentioning
confidence: 99%
“…Although the early paradigm associated with the Mediterranean diet identified moderate alcohol consumption, with red wine as an alcohol source, a growing body of literature shows that the relationship between alcoholic beverages and mortality is rather consistent for both wine and beer, resulting in reduced risk in moderate consumers compared to abstainers or heavy drinkers [44]. Moreover, the results from prospective cohorts suggest that moderate alcohol consumption is inversely associated with risk of hip fractures in middle-aged and older men and women [45]. It should be noted that, in addition to the alcoholic content, these beverages are characterized by a variety of bioactive compounds-mainly polyphenolswhich may explain, at least in part, the potential benefits for health [46].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that frequent or heavy alcohol use in older adults is either positively associated with or inversely associated with fall risks. [29][30][31][32] In this study, drinking alcohol 3 times or more per week was associated with TBI occurrence in men but not in women. The main reason for this result in women is that very few women frequently consumed alcohol, although women can have major physical factors (eg, less lean muscle mass) that make them particularly susceptible to the negative effects of increased alcohol consumption.…”
Section: Discussionmentioning
confidence: 46%
“…Studies have shown that frequent or heavy alcohol use in older adults is either positively associated with or inversely associated with fall risks 29–32. In this study, drinking alcohol 3 times or more per week was associated with TBI occurrence in men but not in women.…”
Section: Discussionmentioning
confidence: 54%
“…Many studies have shown that alcohol affects bone metabolism, not only inhibits bone synthesis, but also increases bone resorption through direct and indirect pathways, leading to osteopenia and osteoporosis, thereby increasing the risk of fractures [24,25]. In our comparative study, we found that the proportion of Spanish women drinking is signi cantly higher than that of Chinese women.…”
Section: Discussionmentioning
confidence: 53%